Waterproof salt-fog-resistant aluminum alloy material and preparation method thereof
By optimizing the aluminum alloy matrix formula and spraying photocuring coatings, the shortcomings of aluminum alloy materials in waterproof and salt spray resistance are solved, and higher salt spray resistance and waterproof performance are achieved.
Patent Information
- Application Number
- CN202510302967.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing aluminum alloy materials have shortcomings in waterproofing and salt spray resistance, which are difficult to meet the needs of use in complex environments.
By adjusting the formulation of the aluminum alloy matrix and spraying light curing coatings on its surface, ultraviolet curing technology can improve the waterproof and salt spray resistance of aluminum alloy materials.
It significantly improves the salt spray corrosion resistance of aluminum alloy materials and enhances its waterproof performance, making it suitable for applications in complex environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, in particular to a waterproof and salt-spray resistant aluminum alloy material and a preparation method thereof. Background Art
[0002] Aluminum alloy is an alloy with aluminum as the matrix and a certain amount of other alloying elements added. It is one of the most widely used light metal materials on the market. Aluminum alloy not only has high strength, but also has good casting performance and plastic processing performance, good electrical and thermal conductivity, and is widely used in aerospace, aviation, transportation, construction, electromechanical, light chemical and daily necessities.
[0003] Nowadays, when aluminum alloys are functionally modified, coatings are generally sprayed on the surface of the aluminum alloys to improve the surface waterproofness and salt spray resistance of the aluminum alloys. Based on this situation, the present application discloses a waterproof and salt spray resistant aluminum alloy material and a preparation method thereof to prepare an aluminum alloy material with excellent salt spray resistance. Summary of the invention
[0004] The object of the present invention is to provide a waterproof and salt spray resistant aluminum alloy material and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a waterproof and salt-spray resistant aluminum alloy material comprises the following steps: Step 1: Mix polyurethane acrylate and styrene, add graphene oxide, stir for 20-30 minutes, then add photoinitiator, stir evenly to obtain a photocurable coating; Step 2: taking an aluminum alloy substrate, ultrasonically cleaning it with acetone for 20 to 30 minutes, ultrasonically cleaning it in deionized water for 20 to 30 minutes, and vacuum drying it. After drying, spraying a light-curing coating on the surface of the aluminum alloy substrate, and curing it with ultraviolet light to obtain the waterproof and salt-spray-resistant aluminum alloy material; The specific components of the aluminum alloy matrix are: in terms of mass fraction, Zn: 0.05%~0.20%, Cr: 0.05%~0.08%, La: 0.08%~0.10%, Si: 0.25%~0.35%, Mn: 0.32%~0.5%, Mg: 1.50%~2.30%, Ti: 0.01%~0.1%, Cu: 0.02%~0.15%, and the rest are Al and unavoidable impurities.
[0006] In a more optimized solution, in step 1, the specific amounts of the components of the photocurable coating are as follows: in parts by mass, 70 to 75 parts of polyurethane acrylate, 28 to 32 parts of styrene, 8 to 10 parts of graphene oxide, and 1 to 3 parts of photoinitiator; the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone.
[0007] In a more optimized solution, in step 1, the preparation steps of polyurethane acrylate are: Step S1: mixing hexafluoropropylene oxide dimer and trifluorotrichloroethane to obtain a hexafluoropropylene oxide dimer solution; Pentaerythritol diacrylate, triethylamine and dichloromethane are mixed, stirred in an ice-water bath until dissolved, and then a hexafluoropropylene oxide dimer solution is added, reacted at 20-25°C for 3-4 hours, rotary evaporated, washed and dried to obtain a terminal hydroxyl fluorinated monomer; Step S2: isophorone diisocyanate and dibutyltin dilaurate are mixed, a hydroxyl-containing functional monomer is added, the mixture is reacted at 60-70° C. for 4-6 hours, phthalic anhydride polyester polyol is added, the mixture is heated at 70-80° C. for 3-5 hours, and after the reaction, styrene is diluted to obtain polyurethane acrylate; the hydroxyl-containing functional monomer is a compound of a terminal hydroxyl fluorine-containing monomer and hydroxypropyl acrylate.
[0008] In a more optimized solution, in step S1, the molar ratio of pentaerythritol diacrylate, hexafluoropropylene oxide dimer and triethylamine is 1: (1.2-1.4): (2.8-3).
[0009] In a more optimized scheme, in step S2, the molar ratio of the terminal hydroxyl fluorinated monomer to hydroxypropyl acrylate is 1:1; the molar ratio of the isophorone diisocyanate to the hydroxyl functional monomer is 1:1; and the molar ratio of the isophorone diisocyanate to the phthalic anhydride polyester polyol is (2-4):1.
[0010] In a more optimized solution, in step S2, the molecular weight of the phthalic anhydride polyester polyol is 400-600; and the functionality of the phthalic anhydride polyester polyol is 2-4.
[0011] In a more optimized scheme, in step S1, the preparation steps of pentaerythritol diacrylate are: acrylic acid, pentaerythritol, a catalyst, an inhibitor and toluene are mixed, stirred evenly, heated to 110-120°C, refluxed for reaction for 3-4 hours, and after the reaction is completed, a saturated sodium chloride solution and a toluene solution are added, filtered in layers, and the filtrate is neutralized with sodium hydroxide (concentration of 5wt%) to a pH of 7, washed with distilled water, and the solvent is removed by reduced pressure distillation to obtain pentaerythritol diacrylate.
[0012] In a more optimized solution, the molar ratio of acrylic acid to pentaerythritol is (2.5-2.6):1; the catalyst is p-toluenesulfonic acid, and the amount of the catalyst is 2wt%-2.5wt% of the total mass of the system; the inhibitor is a compound of hydroquinone and anhydrous copper sulfate, and the mass ratio of hydroquinone to anhydrous copper sulfate is 1:1; the amount of the inhibitor is 2wt%-2.5wt% of the total mass of the system; and the amount of toluene is 40wt%-50wt% of the total mass of the system.
[0013] A more optimized solution is a waterproof and salt spray resistant aluminum alloy material prepared according to any of the preparation methods described above.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The invention discloses a waterproof and salt-spray resistant aluminum alloy material and a preparation method thereof. The scheme adjusts and optimizes the formula of an aluminum alloy matrix, and the final aluminum alloy matrix formula is defined as "the components of the aluminum alloy matrix are specifically: in terms of mass fraction, Zn: 0.05%-0.20%, Cr: 0.05%-0.08%, La: 0.08%-0.10%, Si: 0.25%-0.35%, Mn: 0.32%-0.5%, Mg: 1.50%-2.30%, Ti: 0.01%-0.1%, Cu: 0.02%-0.15%, and the rest are Al and unavoidable impurities"; the aluminum alloy matrix prepared by the formula has excellent comprehensive performance; on this basis, the aluminum alloy matrix is cleaned, and a light-curing coating is sprayed on its surface and cured by ultraviolet light, thereby further improving the salt-spray corrosion resistance of the aluminum alloy material.
[0015] In the scheme, pentaerythritol diacrylate and hexafluoropropylene oxide dimer are first used as raw materials, and through the esterification reaction between the acyl fluoride group and the hydroxyl group, and the molar ratio of the pentaerythritol diacrylate and the hexafluoropropylene oxide dimer is controlled to be 1: (1.2~1.4) to prepare a terminal hydroxyl group-containing fluorine-containing monomer. At this time, not only the fluorine group is introduced into the system, but also the terminal hydroxyl group is retained, which enables the terminal hydroxyl group-containing fluorine-containing monomer to participate in the subsequent polymerization reaction.
[0016] Furthermore, the scheme utilizes the isocyanate group of isophorone diisocyanate, the hydroxyl group of the terminal hydroxyl fluorinated monomer, and the hydroxyl group of hydroxypropyl acrylate to react, and the scheme specifies that "the molar ratio of isophorone diisocyanate and the hydroxyl-containing functional monomer is 1:1", at this time, isophorone diisocyanate is used as a bridge, and one end reacts with the hydroxyl group of the terminal hydroxyl fluorinated monomer or the hydroxyl group of hydroxypropyl acrylate; subsequently, phthalic anhydride polyester polyol is added, and it is specified that "the molar ratio of isophorone diisocyanate and phthalic anhydride polyester polyol is (2~4):1", thereby generating a polyurethane acrylate with phthalic anhydride polyester polyol as the core, isophorone diisocyanate as a bridge, and containing multiple vinyl groups at the end. The polymer is used as the main resin of the photocurable coating, and styrene, graphene oxide and a photoinitiator are added to obtain a photocurable coating to ensure the salt spray resistance and waterproof properties of the aluminum alloy material.
[0017] The plan also limits the "molecular weight of phthalic anhydride polyester polyol to 400~600; the functionality of phthalic anhydride polyester polyol to 2~4". After many tests, it was found that when phthalic anhydride polyester polyol is a mixture of 2-functionality phthalic anhydride polyester polyol and 3-functionality phthalic anhydride polyester polyol, and the molar ratio of 2-functionality phthalic anhydride polyester polyol is limited to 75%, the surface salt spray resistance of the aluminum alloy material is the best. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] In the following examples, the molecular weight of phthalic anhydride polyester polyol is 400. The photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone. The graphene oxide model is XF224-1, which is provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0020] Embodiment 1: A method for preparing a waterproof and salt spray resistant aluminum alloy material, comprising the following steps: Step 1: The preparation steps of polyurethane acrylate are: Step S1: 2.5 mol of acrylic acid, 1 mol of pentaerythritol, a catalyst, an inhibitor and toluene are mixed, stirred evenly, heated to 110°C, refluxed for 4 hours, and after the reaction is completed, a saturated sodium chloride solution and a toluene solution are added, filtered in layers, and the filtrate is neutralized with sodium hydroxide (concentration of 5wt%) to a pH of 7, washed with distilled water, and the solvent is removed by reduced pressure distillation to obtain pentaerythritol diacrylate. The catalyst is p-toluenesulfonic acid, and the amount of the catalyst is 2.5wt% of the total mass of the system; the inhibitor is a compound of hydroquinone and anhydrous copper sulfate, and the mass ratio of hydroquinone to anhydrous copper sulfate is 1:1; the amount of the inhibitor is 2wt% of the total mass of the system; and the amount of toluene is 50wt% of the total mass of the system.
[0021] Mix 0.13 mol of hexafluoropropylene oxide dimer and 10 mL of trifluorotrichloroethane to obtain a hexafluoropropylene oxide dimer solution; 0.1 mol of pentaerythritol diacrylate, 0.3 mol of triethylamine and 100 mL of dichloromethane were mixed, stirred in an ice-water bath until dissolved, and then hexafluoropropylene oxide dimer solution was added, reacted at 20° C. for 4 h, rotary evaporated, washed and dried to obtain a terminal hydroxyl fluorinated monomer.
[0022] Step S2: isophorone diisocyanate and dibutyltin dilaurate are mixed, a hydroxyl functional monomer is added, the mixture is reacted at 60° C. for 6 hours, phthalic anhydride polyester polyol is added, the mixture is heated at 70° C. for 5 hours, and after the reaction is completed, styrene is used to dilute the mixture to obtain polyurethane acrylate.
[0023] The hydroxyl functional monomer is a compound of a terminal hydroxyl fluorine-containing monomer and hydroxypropyl acrylate, wherein the molar ratio of the terminal hydroxyl fluorine-containing monomer to hydroxypropyl acrylate is 1:1; the molar ratio of the isophorone diisocyanate to the hydroxyl functional monomer is 1:1; the molar ratio of the isophorone diisocyanate to the phthalic anhydride polyester polyol is 2:1. The functionality of the phthalic anhydride polyester polyol is 2.
[0024] Step S3: By mass, 72 parts of polyurethane acrylate and 28 parts of styrene are mixed, 8 parts of graphene oxide are added, and the mixture is stirred for 20 minutes. Then, 2.5 parts of photoinitiator are added and stirred evenly to obtain a photocurable coating.
[0025] Step 2: Take the aluminum alloy substrate, ultrasonically clean it in acetone for 20 minutes, then ultrasonically clean it in deionized water for 20 minutes, vacuum dry it, spray light-curing coating on the surface of the aluminum alloy substrate after drying, and cure it with ultraviolet light to obtain the waterproof and salt-spray resistant aluminum alloy material; the spraying thickness is 50μm. When curing, first level it for 5 minutes, preheat it at 50℃ for 30 minutes, and then irradiate it under 800W ultraviolet light for 30 seconds, with a lamp distance of 15cm.
[0026] The specific components of the aluminum alloy matrix are: in terms of mass fraction, Zn: 0.12%, Cr: 0.08%, La: 0.10%, Si: 0.3%, Mn: 0.35%, Mg: 2.0%, Ti: 0.05%, Cu: 0.12%, and the rest are Al and unavoidable impurities. Embodiment 2: A method for preparing a waterproof and salt spray resistant aluminum alloy material, comprising the following steps: Step 1: The preparation steps of polyurethane acrylate are: Step S1: 2.5 mol of acrylic acid, 1 mol of pentaerythritol, a catalyst, an inhibitor and toluene are mixed, stirred evenly, heated to 115°C, and refluxed for 3.5 hours. After the reaction is completed, a saturated sodium chloride solution and a toluene solution are added, filtered in layers, and the filtrate is neutralized with sodium hydroxide (concentration of 5wt%) to a pH of 7, washed with distilled water, and the solvent is removed by reduced pressure distillation to obtain pentaerythritol diacrylate. The catalyst is p-toluenesulfonic acid, and the amount of the catalyst is 2.5wt% of the total mass of the system; the inhibitor is a compound of hydroquinone and anhydrous copper sulfate, and the mass ratio of hydroquinone to anhydrous copper sulfate is 1:1; the amount of the inhibitor is 2wt% of the total mass of the system; and the amount of toluene is 50wt% of the total mass of the system.
[0027] Mix 0.13 mol of hexafluoropropylene oxide dimer and 10 mL of trifluorotrichloroethane to obtain a hexafluoropropylene oxide dimer solution; 0.1 mol of pentaerythritol diacrylate, 0.3 mol of triethylamine and 100 mL of dichloromethane were mixed, stirred in an ice-water bath until dissolved, and then hexafluoropropylene oxide dimer solution was added, reacted at 25° C. for 3.5 hours, rotary evaporated, washed and dried to obtain a terminal hydroxyl fluorinated monomer.
[0028] Step S2: isophorone diisocyanate and dibutyltin dilaurate are mixed, a hydroxyl functional monomer is added, the mixture is reacted at 65° C. for 5 h, phthalic anhydride polyester polyol is added, the mixture is heated at 75° C. for 4 h, and after the reaction is completed, styrene is used to dilute the mixture to obtain polyurethane acrylate.
[0029] The hydroxyl functional monomer is a compound of a terminal hydroxyl fluorine-containing monomer and hydroxypropyl acrylate, wherein the molar ratio of the terminal hydroxyl fluorine-containing monomer to hydroxypropyl acrylate is 1:1; the molar ratio of the isophorone diisocyanate to the hydroxyl functional monomer is 1:1; the molar ratio of the isophorone diisocyanate to the phthalic anhydride polyester polyol is 2:1. The functionality of the phthalic anhydride polyester polyol is 2.
[0030] Step S3: By mass, 72 parts of polyurethane acrylate and 28 parts of styrene were mixed, 9 parts of graphene oxide were added, and the mixture was stirred for 25 minutes. Then, 2.5 parts of photoinitiator were added and stirred evenly to obtain a photocurable coating.
[0031] Step 2: Take the aluminum alloy substrate, ultrasonically clean it in acetone for 25 minutes, then ultrasonically clean it in deionized water for 25 minutes, and vacuum dry it. After drying, spray a light-curing coating on the surface of the aluminum alloy substrate, and cure it with ultraviolet light to obtain the waterproof and salt-spray-resistant aluminum alloy material; the spraying thickness is 50 μm. During curing, first level it for 5 minutes, preheat it at 50°C for 30 minutes, and then irradiate it under 800W ultraviolet light for 30 seconds, with a lamp distance of 15 cm.
[0032] The specific components of the aluminum alloy matrix are: in terms of mass fraction, Zn: 0.12%, Cr: 0.08%, La: 0.10%, Si: 0.3%, Mn: 0.35%, Mg: 2.0%, Ti: 0.05%, Cu: 0.12%, and the rest are Al and unavoidable impurities. Embodiment 3: A method for preparing a waterproof and salt spray resistant aluminum alloy material, comprising the following steps: Step 1: The preparation steps of polyurethane acrylate are: Step S1: 2.5 mol of acrylic acid, 1 mol of pentaerythritol, a catalyst, an inhibitor and toluene are mixed, stirred evenly, heated to 120°C, refluxed for 3 hours, and after the reaction, a saturated sodium chloride solution and a toluene solution are added, filtered in layers, and the filtrate is neutralized with sodium hydroxide (concentration of 5wt%) to a pH of 7, washed with distilled water, and the solvent is removed by reduced pressure distillation to obtain pentaerythritol diacrylate. The catalyst is p-toluenesulfonic acid, and the amount of the catalyst is 2.5wt% of the total mass of the system; the inhibitor is a compound of hydroquinone and anhydrous copper sulfate, and the mass ratio of hydroquinone to anhydrous copper sulfate is 1:1; the amount of the inhibitor is 2wt% of the total mass of the system; and the amount of toluene is 50wt% of the total mass of the system.
[0033] Mix 0.13 mol of hexafluoropropylene oxide dimer and 10 mL of trifluorotrichloroethane to obtain a hexafluoropropylene oxide dimer solution; 0.1 mol of pentaerythritol diacrylate, 0.3 mol of triethylamine and 100 mL of dichloromethane were mixed, stirred in an ice-water bath until dissolved, and then hexafluoropropylene oxide dimer solution was added, reacted at 25° C. for 3 h, rotary evaporated, washed and dried to obtain a terminal hydroxyl fluorinated monomer.
[0034] Step S2: isophorone diisocyanate and dibutyltin dilaurate are mixed, a hydroxyl functional monomer is added, the mixture is reacted at 70° C. for 4 hours, phthalic anhydride polyester polyol is added, the mixture is heated at 80° C. for 3 hours, and after the reaction is completed, styrene is used to dilute the mixture to obtain polyurethane acrylate.
[0035] The hydroxyl functional monomer is a compound of a terminal hydroxyl fluorine-containing monomer and hydroxypropyl acrylate, wherein the molar ratio of the terminal hydroxyl fluorine-containing monomer to hydroxypropyl acrylate is 1:1; the molar ratio of the isophorone diisocyanate to the hydroxyl functional monomer is 1:1; the molar ratio of the isophorone diisocyanate to the phthalic anhydride polyester polyol is 3:1. The functionality of the phthalic anhydride polyester polyol is 3.
[0036] Step S3: By mass, 72 parts of polyurethane acrylate and 28 parts of styrene were mixed, 9 parts of graphene oxide were added, and the mixture was stirred for 30 minutes. Then, 2.5 parts of photoinitiator were added and stirred evenly to obtain a photocurable coating.
[0037] Step 2: Take the aluminum alloy substrate, ultrasonically clean it in acetone for 30 minutes, then ultrasonically clean it in deionized water for 30 minutes, vacuum dry it, spray light-curing coating on the surface of the aluminum alloy substrate after drying, and cure it with ultraviolet light to obtain the waterproof and salt-spray resistant aluminum alloy material; the spraying thickness is 50μm. During curing, first level it for 5 minutes, preheat it at 50℃ for 30 minutes, and then irradiate it under 800W ultraviolet light for 30 seconds, with the lamp distance of 15cm.
[0038] The specific components of the aluminum alloy matrix are: in terms of mass fraction, Zn: 0.12%, Cr: 0.08%, La: 0.10%, Si: 0.3%, Mn: 0.35%, Mg: 2.0%, Ti: 0.05%, Cu: 0.12%, and the rest are Al and unavoidable impurities. Embodiment 4: A method for preparing a waterproof and salt spray resistant aluminum alloy material, comprising the following steps: Step 1: The preparation steps of polyurethane acrylate are: Step S1: 2.5 mol of acrylic acid, 1 mol of pentaerythritol, a catalyst, an inhibitor and toluene are mixed, stirred evenly, heated to 120°C, refluxed for 3 hours, and after the reaction, a saturated sodium chloride solution and a toluene solution are added, filtered in layers, and the filtrate is neutralized with sodium hydroxide (concentration of 5wt%) to a pH of 7, washed with distilled water, and the solvent is removed by reduced pressure distillation to obtain pentaerythritol diacrylate. The catalyst is p-toluenesulfonic acid, and the amount of the catalyst is 2.5wt% of the total mass of the system; the inhibitor is a compound of hydroquinone and anhydrous copper sulfate, and the mass ratio of hydroquinone to anhydrous copper sulfate is 1:1; the amount of the inhibitor is 2wt% of the total mass of the system; and the amount of toluene is 50wt% of the total mass of the system.
[0039] Mix 0.13 mol of hexafluoropropylene oxide dimer and 10 mL of trifluorotrichloroethane to obtain a hexafluoropropylene oxide dimer solution; 0.1 mol of pentaerythritol diacrylate, 0.3 mol of triethylamine and 100 mL of dichloromethane were mixed, stirred in an ice-water bath until dissolved, and then hexafluoropropylene oxide dimer solution was added, reacted at 25° C. for 3 h, rotary evaporated, washed and dried to obtain a terminal hydroxyl fluorinated monomer.
[0040] Step S2: isophorone diisocyanate and dibutyltin dilaurate are mixed, a hydroxyl functional monomer is added, the mixture is reacted at 70° C. for 4 hours, phthalic anhydride polyester polyol is added, the mixture is heated at 80° C. for 3 hours, and after the reaction is completed, styrene is used to dilute the mixture to obtain polyurethane acrylate.
[0041] The hydroxyl functional monomer is a compound of a terminal hydroxyl fluorinated monomer and hydroxypropyl acrylate, and the molar ratio of the terminal hydroxyl fluorinated monomer to hydroxypropyl acrylate is 1:1; the molar ratio of the isophorone diisocyanate to the hydroxyl functional monomer is 1:1; the molar ratio of the isophorone diisocyanate to the phthalic anhydride polyester polyol is 3:1. The phthalic anhydride polyester polyol is a mixture of a phthalic anhydride polyester polyol with a difunctionality and a phthalic anhydride polyester polyol with a trifunctionality, wherein the molar ratio of the difunctionality phthalic anhydride polyester polyol is 75%.
[0042] Step S3: By mass, 72 parts of polyurethane acrylate and 28 parts of styrene were mixed, 10 parts of graphene oxide were added, and the mixture was stirred for 30 minutes. Then, 2.5 parts of photoinitiator were added and stirred evenly to obtain a photocurable coating.
[0043] Step 2: Take the aluminum alloy substrate, ultrasonically clean it in acetone for 30 minutes, then ultrasonically clean it in deionized water for 30 minutes, vacuum dry it, spray light-curing coating on the surface of the aluminum alloy substrate after drying, and cure it with ultraviolet light to obtain the waterproof and salt-spray resistant aluminum alloy material; the spraying thickness is 50μm. During curing, first level it for 5 minutes, preheat it at 50℃ for 30 minutes, and then irradiate it under 800W ultraviolet light for 30 seconds, with the lamp distance of 15cm.
[0044] The specific components of the aluminum alloy matrix are: in terms of mass fraction, Zn: 0.12%, Cr: 0.08%, La: 0.10%, Si: 0.3%, Mn: 0.35%, Mg: 2.0%, Ti: 0.05%, Cu: 0.12%, and the rest are Al and unavoidable impurities. Comparative Example 1: Comparative Example 1 is a control experiment based on Example 3, in which the hydroxyl functional monomer is a terminal hydroxyl fluorine-containing monomer, hydroxypropyl acrylate is not added for compounding, and the other steps remain unchanged.
[0045] A method for preparing a waterproof and salt-spray resistant aluminum alloy material comprises the following steps: Step 1: The preparation steps of polyurethane acrylate are: Step S1: 2.5 mol of acrylic acid, 1 mol of pentaerythritol, a catalyst, an inhibitor and toluene are mixed, stirred evenly, heated to 120°C, refluxed for 3 hours, and after the reaction, a saturated sodium chloride solution and a toluene solution are added, filtered in layers, and the filtrate is neutralized with sodium hydroxide (concentration of 5wt%) to a pH of 7, washed with distilled water, and the solvent is removed by reduced pressure distillation to obtain pentaerythritol diacrylate. The catalyst is p-toluenesulfonic acid, and the amount of the catalyst is 2.5wt% of the total mass of the system; the inhibitor is a compound of hydroquinone and anhydrous copper sulfate, and the mass ratio of hydroquinone to anhydrous copper sulfate is 1:1; the amount of the inhibitor is 2wt% of the total mass of the system; and the amount of toluene is 50wt% of the total mass of the system.
[0046] Mix 0.13 mol of hexafluoropropylene oxide dimer and 10 mL of trifluorotrichloroethane to obtain a hexafluoropropylene oxide dimer solution; 0.1 mol of pentaerythritol diacrylate, 0.3 mol of triethylamine and 100 mL of dichloromethane were mixed, stirred in an ice-water bath until dissolved, and then hexafluoropropylene oxide dimer solution was added, reacted at 25° C. for 3 h, rotary evaporated, washed and dried to obtain a terminal hydroxyl fluorinated monomer.
[0047] Step S2: isophorone diisocyanate and dibutyltin dilaurate are mixed, a terminal hydroxyl fluorinated monomer is added, the mixture is reacted at 70° C. for 4 h, phthalic anhydride polyester polyol is added, the mixture is heated at 80° C. for 3 h, and after the reaction is completed, styrene is used to dilute the mixture to obtain polyurethane acrylate.
[0048] The molar ratio of isophorone diisocyanate to terminal hydroxyl fluorinated monomer is 1:1; the molar ratio of isophorone diisocyanate to phthalic anhydride polyester polyol is 3:1. The functionality of phthalic anhydride polyester polyol is 3.
[0049] Step S3: By mass, 72 parts of polyurethane acrylate and 28 parts of styrene were mixed, 9 parts of graphene oxide were added, and the mixture was stirred for 30 minutes. Then, 2.5 parts of photoinitiator were added and stirred evenly to obtain a photocurable coating.
[0050] Step 2: Take the aluminum alloy substrate, ultrasonically clean it in acetone for 30 minutes, then ultrasonically clean it in deionized water for 30 minutes, vacuum dry it, spray light-curing coating on the surface of the aluminum alloy substrate after drying, and cure it with ultraviolet light to obtain the waterproof and salt-spray resistant aluminum alloy material; the spraying thickness is 50μm. During curing, first level it for 5 minutes, preheat it at 50℃ for 30 minutes, and then irradiate it under 800W ultraviolet light for 30 seconds, with the lamp distance of 15cm.
[0051] The specific components of the aluminum alloy matrix are: in terms of mass fraction, Zn: 0.12%, Cr: 0.08%, La: 0.10%, Si: 0.3%, Mn: 0.35%, Mg: 2.0%, Ti: 0.05%, Cu: 0.12%, and the rest are Al and unavoidable impurities. Comparative Example 2: Comparative Example 2 is a control experiment based on Example 3, in which the terminal hydroxyl fluorine-containing monomer is replaced by pentaerythritol triacrylate, and hydroxypropyl acrylate is not added for compounding, and the other steps remain unchanged.
[0052] Step 1: The preparation steps of polyurethane acrylate are: Step S1: isophorone diisocyanate and dibutyltin dilaurate are mixed, pentaerythritol triacrylate is added, the mixture is reacted at 70° C. for 4 hours, phthalic anhydride polyester polyol is added, the mixture is heated at 80° C. for 3 hours, and after the reaction is completed, styrene is used for dilution to obtain polyurethane acrylate.
[0053] The molar ratio of isophorone diisocyanate to pentaerythritol triacrylate is 1:1; the molar ratio of isophorone diisocyanate to phthalic anhydride polyester polyol is 3:1. The functionality of phthalic anhydride polyester polyol is 3.
[0054] Step S2: By mass, 72 parts of polyurethane acrylate and 28 parts of styrene were mixed, 9 parts of graphene oxide were added, and the mixture was stirred for 30 minutes. Then, 2.5 parts of photoinitiator were added and stirred evenly to obtain a photocurable coating.
[0055] Step 2: Take the aluminum alloy substrate, ultrasonically clean it in acetone for 30 minutes, then ultrasonically clean it in deionized water for 30 minutes, vacuum dry it, spray light-curing coating on the surface of the aluminum alloy substrate after drying, and cure it with ultraviolet light to obtain the waterproof and salt-spray resistant aluminum alloy material; the spraying thickness is 50μm. During curing, first level it for 5 minutes, preheat it at 50℃ for 30 minutes, and then irradiate it under 800W ultraviolet light for 30 seconds, with the lamp distance of 15cm.
[0056] The specific components of the aluminum alloy matrix are: in terms of mass fraction, Zn: 0.12%, Cr: 0.08%, La: 0.10%, Si: 0.3%, Mn: 0.35%, Mg: 2.0%, Ti: 0.05%, Cu: 0.12%, and the rest are Al and unavoidable impurities.
[0057] Detection experiment: 1. Take the aluminum alloy samples prepared by the methods of Examples 1 to 4 and Comparative Examples 1 to 2, and test the adhesion performance of the light-curing coating with reference to GB / T9286-2021 "Scratch test for paint and varnish films"; test the hardness with reference to GBT6739-2022 "Determination of paint film hardness by pencil method for paint and varnish".
[0058] Waterproofness: Soak the aluminum alloy sample in deionized water for 72 hours at a test temperature of 30°C, and observe whether the paint film on the surface of the sample has blistering, discoloration, cracking, etc. If there is no blistering, discoloration, cracking, etc., it is considered qualified; otherwise, it is considered unqualified.
[0059] Neutral salt spray test: refer to the method disclosed in GB / T1771-2007 "Determination of neutral salt spray resistance of paints and varnishes", the test temperature in the salt spray chamber is 35°C, the corrosive medium is 5wt% NaCl solution, and the time for bubbling of the paint film on the sample surface is observed.
[0060] The specific data are shown in Table 1, where “ / ” in the table means not tested or not recorded.
[0061] Table 1
[0062] Conclusion: The scheme adjusted and optimized the formula of the aluminum alloy matrix. The final formula of the aluminum alloy matrix was limited to "the components of the aluminum alloy matrix are: by mass fraction, Zn: 0.05%~0.20%, Cr: 0.05%~0.08%, La: 0.08%~0.10%, Si: 0.25%~0.35%, Mn: 0.32%~0.5%, Mg: 1.50%~2.30%, Ti: 0.01%~0.1%, Cu: 0.02%~0.15%, and the rest are Al and unavoidable impurities"; the aluminum alloy matrix prepared by this formula has excellent comprehensive performance; on this basis, the aluminum alloy matrix is cleaned, and a light-curing coating is sprayed on its surface and cured by ultraviolet light, thereby further improving the salt spray corrosion resistance of the aluminum alloy material.
[0063] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A method for preparing a waterproof and salt spray resistant aluminum alloy material, characterized in that: The following steps are involved: Step 1: Mix polyurethane acrylate and styrene, add graphene oxide, stir for 20-30 minutes, then add photoinitiator, stir evenly to obtain a photocurable coating; Step 2: taking an aluminum alloy substrate, ultrasonically cleaning it with acetone for 20 to 30 minutes, ultrasonically cleaning it in deionized water for 20 to 30 minutes, and vacuum drying it. After drying, spraying a light-curing coating on the surface of the aluminum alloy substrate, and curing it with ultraviolet light to obtain the waterproof and salt-spray-resistant aluminum alloy material; The specific components of the aluminum alloy matrix are: in terms of mass fraction, Zn: 0.05%~0.20%, Cr: 0.05%~0.08%, La: 0.08%~0.10%, Si: 0.25%~0.35%, Mn: 0.32%~0.5%, Mg: 1.50%~2.30%, Ti: 0.01%~0.1%, Cu: 0.02%~0.15%, and the rest are Al and unavoidable impurities.
2. The method for preparing a waterproof and salt spray resistant aluminum alloy material according to claim 1, characterized in that: In step 1, the specific amounts of the components of the photocurable coating are as follows: by mass, 70-75 parts of polyurethane acrylate, 28-32 parts of styrene, 8-10 parts of graphene oxide, and 1-3 parts of photoinitiator; the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone.
3. The method for preparing a waterproof and salt spray resistant aluminum alloy material according to claim 1, characterized in that: In step 1, the preparation steps of polyurethane acrylate are: Step S1: mixing hexafluoropropylene oxide dimer and trifluorotrichloroethane to obtain a hexafluoropropylene oxide dimer solution; Pentaerythritol diacrylate, triethylamine and dichloromethane are mixed, stirred in an ice-water bath until dissolved, and then a hexafluoropropylene oxide dimer solution is added, reacted at 20-25°C for 3-4 hours, rotary evaporated, washed and dried to obtain a terminal hydroxyl fluorinated monomer; Step S2: isophorone diisocyanate and dibutyltin dilaurate are mixed, a hydroxyl functional monomer is added, the mixture is reacted at 60-70° C. for 4-6 hours, phthalic anhydride polyester polyol is added, the mixture is heated at 70-80° C. for 3-5 hours, and after the reaction is completed, styrene is diluted to obtain polyurethane acrylate; The hydroxyl functional monomer is a compound of a terminal hydroxyl fluorine-containing monomer and hydroxypropyl acrylate, and the molar ratio of the terminal hydroxyl fluorine-containing monomer to hydroxypropyl acrylate is 1:
1.
4. The method for preparing a waterproof and salt spray resistant aluminum alloy material according to claim 3, characterized in that: In step S1, the molar ratio of pentaerythritol diacrylate, hexafluoropropylene oxide dimer and triethylamine is 1:(1.2-1.4):(2.8-3).
5. The method for preparing a waterproof and salt spray resistant aluminum alloy material according to claim 3, characterized in that: In step S2, the molar ratio of isophorone diisocyanate to the hydroxyl functional monomer is 1:1; the molar ratio of isophorone diisocyanate to phthalic anhydride polyester polyol is (2-4):
1.
6. The method for preparing a waterproof and salt spray resistant aluminum alloy material according to claim 5, characterized in that: In step S2, the molecular weight of the phthalic anhydride polyester polyol is 400-600; the functionality of the phthalic anhydride polyester polyol is 2-4.
7. The method for preparing a waterproof and salt spray resistant aluminum alloy material according to claim 3, characterized in that: In step S1, the preparation step of pentaerythritol diacrylate is: acrylic acid, pentaerythritol, a catalyst, an inhibitor and toluene are mixed, stirred evenly, heated to 110-120° C., refluxed for 3-4 hours, and after the reaction is completed, a saturated sodium chloride solution and a toluene solution are added, the mixture is filtered in layers, the filtrate is neutralized with sodium hydroxide to a pH of 7, washed with distilled water, and the solvent is removed by distillation under reduced pressure to obtain pentaerythritol diacrylate.
8. The method for preparing a waterproof and salt spray resistant aluminum alloy material according to claim 7, characterized in that: The molar ratio of acrylic acid to pentaerythritol is (2.5-2.6):1; the catalyst is p-toluenesulfonic acid, and the amount of the catalyst is 2wt%-2.5wt% of the total mass of the system; the inhibitor is a compound of hydroquinone and anhydrous copper sulfate, and the mass ratio of hydroquinone to anhydrous copper sulfate is 1:1; the amount of the inhibitor is 2wt%-2.5wt% of the total mass of the system.
9. A waterproof and salt spray resistant aluminum alloy material prepared according to the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of anti-aging ultraviolet cured acrylic-polyurethane resin containing fluorine
CN102070767A
Method for preparing UV (Ultraviolet) cured anti-electromagnetic shielding coating based on graphene oxide
CN103788806A
Urethane acrylate oligomer, and preparation method and ultraviolet-curing antifogging coating thereof
CN103980455A
Aluminum alloy for high-strength corrosion-resistant doors and windows and preparation method thereof
CN109161746A
Antifouling photocurable resin composition containing perfluorine polyether modified compound and antifouling transparent thin film for hard coating including same
KR1020140095146A